Imitations of life : two centuries of melodrama in Russia - McReynolds, Louise, 1952-; Neuberger, Joan, 1953- (Duke backfile, 2002)
Uses the under-studied genre of melodrama as a critical prism for understanding Russian/Soviet history, politics and culture--in particular, the uses to which popular culture was put in the Soviet period.